ABOUT INTEGRAL EVALUATION OF THE CONDITION OF LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION IN TOXICOLOGICAL EXPERIMENT - V. V. Benemanskiy; G. G. Yushkov; V. V. Igumenshcheva; O. G. Shchukina (Acta Biomedica Scientifica, 2012)
The article reviews possibility of use of integral index of evaluation of condition of lipid peroxidation and. antioxidant protection processes in toxicological researches. Definite results of use of dihydroquercetin antioxidant at the dicyclopentadiene poisoning are presented.